PENGARUH ORIENTASI PASAR DAN KAPABILITAS INOVASI DALAM MENINGKATKAN NILAI PELANGGAN SERTA DAMPAKNYA TERHADAP KEUNGGULAN BERSAING PERUSAHAAN - Eddi Suprayitno (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2017)
D.I. Yogyakarta is place produce have batik motif and result impact competitive inter place produce have batik motif and international. The main problem faced by Yogya batik is the low customer value of batik Yogya, thus reducing the competitiveness of Yogya batik. This Matter is caused batik industry of Yogya unable to read and analysis change of market that is in fulfilling requirement and desire of this market research. The purpose of this study is to uncover the market orientation and innovation capabilities Yogya batik industry in increasing customer value and competitive advantage. Results of the analysis showed that; market orientation, innovation capabilities Yogya batik industry in the low category. Batik Yogya industry has not been able to identify the needs and desires of customers primarily in the design style and color as well as changes in customer demand. Yogya Batik is still less innovative in product development such as; Product modification, product design and product variety and inefficient production processes. Jogja batik customer value is still dominantly Inferior Customer Value. Yogya Batik industry is still unable to compete with Solo and Pekalongan batik. Batik industry in D.I. Yogayakarta to enhance the competitive advantage necessary for innovation in design pattern (motif), and the color as well as customize what the customer wants and needs batik. Keywords: Market Orientation, Capability Innovation, Customer Value, Competitive Advantage